Looking Good : an Introduction to Industrial Designs for Small and Medium-sized Enterprises. - Organization, World Intellectual Property (IP for Business., 2019)
This is the second in a series of guides on ""Intellectual Property for Business"". It focuses on industrial designs, a key factor in determining the success of products in the market.